Peningkatan Kemampuan Menulis Dialog Sederhana Offering Something Dalam Bahasa Inggris Melalui Model Pembelajaran Picture And Picture Pada Siswa Kelas VII E SMP Negeri 1 Ngablak - Wahyudi, Eko (Faculty Of Education, 2024)
English is one of the foreign languages ​​taught in schools. One of the students' difficulties in learning English as a foreign language is how to write a simple dialogue about offering something correctly. One effort to overcome these student difficulties is by applying various learning models in learning activities. Therefore a Classroom Action Research (CAR) using the Picture and Picture learning model was carried out. The subjects of this study were 27 students in class VII E. Sources of research data obtained from qualitative data and quantitative data. Meanwhile, quantitative data is in the form of skill in writing simple dialogs about offering something. The improvement of students' skill in simple writing about offering something in class VII E students of SMP Negeri 1 Ngablak after implementing the Picture and Picture learning model is as follows: (1) the average score obtained in Pre-Cycle conditions was 69.70 with a learning completeness percentage of 18.52 %, and classical completeness has not been achieved; (2) the average score in Cycle I was 76.07 with a learning completeness percentage of 81.48%, and classical mastery had not been achieved; and (3) the average score in Cycle II was 81.56 with a completeness percentage of 85.19%, and classical completeness had been achieved. From the results of this study, it can be concluded that the implementation of the Picture and Picture learning model can improve students' skill in writing simple dialogues about Offering Something.